KOORDINASI PEMERINTAH DAERAH DALAM PEMBANGUNAN INFRASTRUKTUR JALAN DI KECAMATAN KAO BARAT KABUPATEN HALMAHERA UTARA - NGETJE, HENI; RURU, JOORIE; PLANGITEN, NOVVA (Sam Ratulangi University, 2019)
The purpose of this study is to find out how the coordination of local governments in thedevelopment of road infrastructure in the West Kao District, North Halmahera Regency. This researchuses a descriptive-qualitative approach. Based on the study of coordination theory seen from fourindicators, namely: coordination through authority, coordination through consensus, coordinationthrough work guidelines, and coordination through one forum. The informants of this study were 1person Bappeda Head, 1 person Bappeda Secretary, 1 person Bappeda Officer, 2 PUTR Offices, West KaoSub-district Head and 1 West Kao Sub-district community. The data analysis technique used is aninteractive model analysis of Miles and Hubernam. The results showed: (1) The coordination of theregional government in the construction of the road infrastructure in the West Kao Subdistrict, NorthHalmahera Regency was seen from the coordination through the authority that had run quite well. (2)Seen from the coordination through consensus in the construction of road infrastructure in West KaoDistrict, North Halmahera Regency has also not run optimally. (3) Coordination of local government inthe construction of road infrastructure in West Kao Subdistrict, North Halmahera Regency, seen from thecoordination through work guidelines, has been running quite well, seen from the cooperation betweenthe sub-district government, Bappeda, and the PUTR Office. (4) Coordination through a forum is goodenough seen from the government's work plan in which there is Musrembang.Keywords: Coordination, Development, Road Infrastructure.